The Influence of Self Efficacy on Job Performance Mediated by Intrinsic Work Motivation at Ciputra University Makassar - Cunardy, Kevin; Nabila Taufik; Bella Amalia Sasya Wardani; Carolina Novi Mustikarini (Accounting Profession Journal (APAJI), 2025)
This study is driven by researchers' curiosity regarding the factors influencing the job performance of lecturers and staff at Ciputra University Makassar. This inquiry led to the development and distribution of questionnaires among lecturers and staff as research subjects. The study employs a quantitative approach utilizing the second-order confirmatory factor analysis method. Additionally, a Likert scale is applied to assess respondents' levels of agreement or disagreement. A more comprehensive discussion on the role of motivation in shaping the performance of lecturers and staff at Ciputra University Makassar is presented in the following chapters.